Identification of The Bactericide Active Fraction on Zingiber gramineum Blume Bark - I Made Dira Swantara (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Jember, 2009)
Bactericide fraction as been isolated and identified from Zingiber gramineum Blume bark. The isolation carried out using partition by n-hexane, chloroform, and ethyl acetate eluent. The extract bactericide active (ethyl acetate extract) as been isolated using column chromatograpic method by benzene-chloroform (3:2) eluen system. The activity test of that isolate using Micrococcus luteus and Eschericia coli. The chemical structure of the compound was identified using gas chromatography-spectroscopy massa with Wiley 275.L library. The active fraction for E. coli contain hexadecanoic acid, ethyl ester; linoleic acid, ethyl ester; oleic acid, ethyl ester; and octadecanoic acid, ethyl ester. The active fraction for M. luteus contain octadecnoic acid; 9,12-octadecadienoic acid; octadec-9-enoic acid; and hexadioic acid, dioctyl ester.